Level of Competency among Palestinian Nurses Regarding Electrocardiogram Interpretation and Arrhythmias Management: A Cross-Sectional Study - Qaddumi, Jamal; Omar, Sewar; Alsadi, Ahmad; Kanan, Huthaifah; Mahmoud, Manar; Dwikat, Mohammed (Journal of Health and Allied Sciences NU, 2024)
Background Electrocardiographic (ECG) interpretation skills are key in providing fast attention to patients with cardiovascular diseases, enabling prevention or early detection of life-threatening situations. The main aim of the study is to determine the current competency level in ECG interpretation and arrhythmias management of nurses in critical and noncritical departments.Method A cross-sectional design using a convenience sample of 251 nurses working in critical and noncritical departments of Northern West Bank hospitals was used. A valid and reliable structured questionnaire was used to collect data that were designed to measure the competency level in ECG interpretation and arrhythmias management.Result About half of the participants were females (50.2%), with a mean age of 29.2 ± 5.68 years, and 50.2% of them reported they received ECG courses. Unfortunately, low competency levels in ECG interpretation and arrhythmias management of nurses in critical and noncritical departments were found as only 17.1% of the participants were competent (≥7.5 out of 10). Nurses working in critical care units, males, and those with higher education levels scored significantly higher than those working in noncritical units, females, and those with a bachelor's degree or diploma. Unfortunately, nurses had low competency levels not only in ECG rhythm interpretation but also in the management of arrhythmia cases.Conclusion The level of competency in ECG interpretation and arrhythmias management among Palestinian nurses is low as only 17.1% of participants were competent in ECG interpretation and arrhythmia management. Thus, this can be considered a serious and alarming situation especially when dealing with a malignant lethal arrhythmia. Therefore, improving nurses' knowledge of ECG interpretation and management of cardiac arrhythmias is essential and warranted.
Keywords: ECG; ECG interpretation; arrhythmias; arrhythmias management; competency